Identification of Novel SNPs and 10 bp Deletion of Ovine dgat1 Gene and Their Association with Milk Production Traits - Ozmen, Ozge; Kul, Selim (Chulalongkorn Univ, 2016)
Acyl coenzyme A: diacylglycerol acyltransferase 1 (dgat1) plays a key role in triacylglycerol synthesis by catalyzing the final committed step in the formation of triglycerides. Moreover, it could be used as a positional marker gene associated with milk production and composition traits. The purpose of the study was to identify genotype frequencies of single nucleotide polymorphisms (SNPs) in ovine dgat1 gene and its possible association with milk traits in dairy sheep breeds. The genetic structures of SNPs were examined by PCR-RFLP and DNA sequencing in three sheep populations. Significant association of dgat1 gene of the intron 16 g.8384T>C loci with milk fat percentage and milk yield in Sakiz sheep breed was demonstrated. The present study reported for the first time eight SNPs and a 10 bp deletion (g.8213_8223de1TGGGGCGGGG) in the dgat1 gene and its association with milk traits in dairy sheep breeds. These preliminary results indicate that the identified SNPs and deletion lend themselves readily for further research regarding physiological impacts such as milk production and reproductive traits in other dairy sheep populations.
Keywords: dairy sheep breeds; dgat1 gene; milk traits; SNPs